Genetic relateneá of fonio (Digitaria spp.) landraces aáembled in Ghana - Clottey, V.A.=700 1 Agyare, W.A.; Bayorbor, T.B.; Abanga, J.J.
(En, Fr, Es)
Ilus., 18 ref.
Keywords: POACEAE; DIGITARIA EXILIS; FITOMEJORAMIENTO; VARIACION GENETICA; GHANA